Gardens of Tolerance: Ukrainian Women Artists Reflect the War in the Donbas - Martynyuk, Olena (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2022)
With ongoing war in the Donbas, war narratives and war images saturate public media in Ukraine, the discourse contaminated by ideological remnants of the Soviet World War II cult and by fake news. Art that deals with war wounds can subvert the familiar visual language of war propaganda, where the suffering of victims is a mere pretext for touting the inevitable triumph of the heroes. Currently in Ukraine, the most prolific art in this regard is produced by women-artists who address the trauma of war through painting and installations that offer highly personalized accounts. Often touching upon extreme circumstances, their art is about tolerance, both in terms of endurance and of the mutual understanding necessary for cohabitation. Alevtyna (Alevtina) Kakhidze’s ongoing performance creates an opportunity to comprehend the war in the Donbas from multiple perspectives, including that of a gardener. She associates the tending of plants with her mother who died on occupied territory, refusing to leave her garden. Mariia (Maria) Kulikovs'ka’s sculptures serve as shooting targets for separatists in the occupied centre of contemporary art in Donetsk. Vlada Ralko’s paintings of tortured bodies become a metaphor for scars garnered by a war that remains close to home. Paintings and sculptures by Maryna Skuharieva (Skugareva) and Anna Zviahintseva (Zvyagintseva) address the ruin of representation inflicted by war, and the conceptual performance by Liia (Lia) Dostlieva and Andrii Dostliev contemplates the healing process of war wounds. Neither making spectacle from the “pain of others” nor deeming it unrepresentable, this art seeks emphatic alternatives to traditional war narratives.